Best Answer

Pretty badly formulated question! Try to express yourself more carefully if you want good answers to your questions. Otherwise no one knows what you're even asking, like here.

So let me guess:

2x + 3y + 2(x-y) - 3x seems to be the expression

Let's simplify this thing:

2x + 3y + 2x - 2y - 3x

that's just

2x + 2x - 3x + 3y - 2y

or, using "the distributive property",

(2 + 2 - 3)x + (3 - 2)y

equals

x + y

Q: What is 2x plus 3y plus 2(x-y)-3x distributive property?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2(x+6)=2x+12. This is an example of the distributive property.

No. It is a meaningless equation. You may have intended to say: 2 times the sum of x and g is equal to 2x plus 2g.

7x = 4x+2x+1xSo 7x/2 = 4x/2 + 2x/2 + x/2 (by the distributive property of division over addition) = 2x + x + x/2

2x(a+3b)=2xa+6xb

The distributive property is when you take you number is share it with all the other numbers in the parenthesis. An example is x(2 + 3) = 2x + 3X.

Related questions

6x + 15

2(x+6)=2x+12. This is an example of the distributive property.

2x(3x-1) = 6x2-2x because of the distributive property.

2x(4+8) = 2x(4) and 2x(8)

No. It is a meaningless equation. You may have intended to say: 2 times the sum of x and g is equal to 2x plus 2g.

6x2-2x

7x = 4x+2x+1xSo 7x/2 = 4x/2 + 2x/2 + x/2 (by the distributive property of division over addition) = 2x + x + x/2

2x(a+3b)=2xa+6xb

The distributive property is when you take you number is share it with all the other numbers in the parenthesis. An example is x(2 + 3) = 2x + 3X.

Zero. The sum of anything and it's opposite is zero, that's how an opposite is defined. In this case, the opposite of 2x + 1 is -(2x + 1) = -2x - 1 by the distributive property. Adding like terms, 2x + -2x + 1 +-1 = 0 + 0 = 0.

This uses the distributive property.

The distributive property says that a(b+c) = ab +ac. The "a" out front multiplies everything inside the parentheses, so you can "distribute" it onto the "b" and the "c". For example, 2x(x+3) = 2x(x) + 2x(3) = 2x2 + 6x